Study on histological properties of recellularized bioscaffolds from decellularized tissues for vessel regenerative application - Azhim, Azran; Sha'ban, Munirah; Kitajima, Tatsuo; Mohamad, Saharuddin; Mat Ripen, Adiratna (2019)
The increasing number of arteries and organs needed for cardiovascular disease (CVD) patients with end-stage organ failure and bypass surgery has urge the need for future medical substituents. Transplantation provides an immediate treatment for the patients with end stage of organ failure by replacing tissues or organs with the normally function substitute. However, the need of immunosuppression and shortage of donors limit the impact of transplantation which then propel the evolution of tissue engineering. Recently, sonication decellularization technique is able to to prepare biological decellularized tissue efficiently. It has been established and proven by Azhim et al. and has successfully characterized some properties of the decellularized tissue scaffolds in the previous project (FRGS/1/2015/SG05/UIAM/02/6). However, its remaining research includes recellularized bioscaffolds properties evaluation and in-vitro cell infiltration and proliferation evaluations. It is hypothesized that recellularized bioscaffolds have fully seeded and infiltrated by autologous cells while producing new extracellular matrix (ECM) composition and providing sufficient biomechanical integrity of the ECM before implantation. In previous study, it has demonstrated that the decellularized tissues are able to prepare with lower toxicity level and significantly unchanged biomechanical strength. Henceforth, the objectives of this research are to investigate recellularization rate of the seeded cells onto/ into decellularized bioscaffolds which engineered by sonication decellularization system. The ECM integrity and cell removal of decellularized artery are confirmed by evaluation of histological HE staining, scanning electron microscopy and DNA quantitation. The recellularization of decellularized matrices are evaluated by measuring the coverage of the seeded endothelial cells on the matrices and their capability to infiltrate into the matrices using similar methods as described above. The outcome of this research could give an insight on the potential use of recellularized bioscaffolds in regenerative tissues/organs in future medicine.